2019
DOI: 10.1186/s13287-019-1199-8
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived stem cells promote survival, growth, and maturation of early-stage murine follicles

Abstract: BackgroundPremature ovarian insufficiency is a common complication of anticancer treatments in young women and girls. The ovary is a complex, highly regulated reproductive organ, whose proper function is contingent upon the bidirectional endocrine, paracrine, and autocrine signaling. These factors facilitate the development of the follicles, the functional units of the ovary, to progress from the gonadotropin-independent, paracrine-controlled early stage to the gonadotropin-dependent, endocrine-controlled late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…For the in vivo animal experiment, mouse ADSCs (mADSCs) were isolated from the subcutaneous adipose tissue in groin of C57BL/6 mouse [ 32 ]. The methods for conditioned medium of mADSCs (mADSC-CM) collection and the fabrication for mADSC-CM loaded electrospun membranes is the same as that we described in the section of experiments in vitro .…”
Section: Methodsmentioning
confidence: 99%
“…For the in vivo animal experiment, mouse ADSCs (mADSCs) were isolated from the subcutaneous adipose tissue in groin of C57BL/6 mouse [ 32 ]. The methods for conditioned medium of mADSCs (mADSC-CM) collection and the fabrication for mADSC-CM loaded electrospun membranes is the same as that we described in the section of experiments in vitro .…”
Section: Methodsmentioning
confidence: 99%
“…It was shown that ATDCs can promote the early stages of follicles survival, growth and maturation. They secret factors which promote the early stages of follicle growth (50). Also, AFDCs have shown to preserve ovarian follicle after chemotherapy (51) and they have potential to differentiate into primordial follicle (52).…”
Section: Discussionmentioning
confidence: 99%
“…As we all know, cell therapy strategy has been reported to be a strongly effective way in the treatment of different diseases [16,18,33,34]. MSCs act as a kind of adult stem/stromal cells that could differentiate into specific tissues cells induced by local microenvironment when they were damaged, and could secrete various cytokines.…”
Section: Discussionmentioning
confidence: 99%